The Needs Analysis for Developing Student Worksheets of Fairytale Appreciation Based on the P-IKADKA Model - Yesi Azzahra; Seni Apriliya; Dwi Alia (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to analyze the needs for developing worksheets in learning to appreciate fairytales based on the P-IKADKA Model in elementary schools. In accordance with this objective, the approach used is descriptive qualitative, data was collected through observation, interviews, documentation studies, and literature study. The findings show that learning to appreciate fairytales has not been fully implemented in an appreciative manner, learning has only been carried out to the understanding stage, not yet to the stage of responding to and assessing the content of fairytales. Apart from that, it was found that the availability of worksheets for fairytale appreciation has not been able to facilitate comprehensive appreciation covering all stages, this is because teachers only refer to source books from the Kemendibudristek. Referring to the problems and needs, it is necessary to develop worksheets for learning fairytale appreciation based on the P-IKADKA model. This learning model was chosen because it was considered appropriate for learning fairytale appreciation. The development of this worksheets aims to facilitate learning to appreciate fairytales, as well as as a tool for teachers to guide students in understanding concepts through the activities contained in the worksheets.